Trends in Research on Critical and Spatial Thinking Profiles in Mathematics in Indonesia (2015–2025) - Kurniawati, Reny; Neni Mariana,; Dr.Endah Budi Rahaju, M.Pd.; Dr. Nurul Istiq'faroh, M.Pd. (Elementary Teacher Education Program, Majalengka University, 2025)
Research on critical and spatial thinking in mathematics in Indonesia has experienced significant development over the past decade. Initially, most studies emphasized the characteristics and indicators of critical thinking, while research on spatial abilities was relatively limited. However, as 21st-century education increasingly demands higher-order thinking skills, including the ability to visualize, interpret, and analyze spatial relationships, interest in spatial thinking research has grown. This study aims to analyze the trends and patterns of research on the critical and spatial thinking profiles in mathematics education in Indonesia using bibliometric analysis with VOSviewer. The data were collected from the Dimensions AI database by searching the keyword “Critical and spatial thinking profile in mathematics in Indonesia.” A total of 291 documents were initially identified, and after filtering by publication year (2015–2025) and relevance, 279 were selected for analysis. The results show a consistent increase in publication and citation activity, especially from 2018 to 2024, with 24 citations recorded in 2025 alone. Network visualization reveals strong linkages between frequently used terms, indicating interconnected research themes across different studies and years. Overlay visualization highlights shifts in research focus over time, while density visualization identifies clusters with the highest publication concentration. These three visualization techniques offer comprehensive insights into the development of this research area. They assist researchers in discovering new themes, identifying gaps in the literature, and uncovering potential directions for future studies, especially in the context of incorporating critical and spatial thinking abilities into effective mathematics instruction across different levels of education.